Reflection of family values in the Tatar Paramias: east and western traditions - Akhmetova, Elmira (Magnanimitas, 2017)
Folklore texts of different peoples of the world have repeatedly been the subject of study of scientists in different branches of science. Along with bylinas, fairy tales, and parables, which show the main mental qualities of the people, the aphoristic genres have been studied. After all, proverbs, sayings, rhymes from ancient times played an important role in the spiritual life of the people, now have their cognitive, aesthetic influence in the upbringing of the new generation. Therefore, their scientific potential is not exhausted for further research, since they show the traditional culture of the people, their mentality. Despite the fact that the paramias of different peoples have much in common, there are still differences, coming from different cultures and showing the national orientation of a representative of a given culture. It is believed that the culture of the Tatar people reflects Western and Eastern cultures. Due to historical and geographical factors of the place of residence, the Tatars are on the junction of these two major civilizations. Therefore, their culture has both Western and Eastern traits of knowledge of the world, which was reissued through life experiences, and is reflected in different aspects of life. The aim of this work was to study the reflections of Western and Eastern cultures in determining the values of the Tatars. The object of the study are paramias of the Tatar language. Family values of the Tatar people are the subject of the study. The author uses descriptive, comparativedescriptive, integrated-contrastive, statistical and linguistic and cultural research methods. We believe that the results of the study will be useful to ethnolinguists, culturologists, historians, and also for a wide range of readers interested in linguostylistics and Ethnology. It should be said that the obtained results of paremiological material showed that the Tatars have their own vision and understanding of the tenets of loyalty, love, duty and purpose of life.